Influence of pore water in the seabed on dynamic response of offshore wind turbines on monopiles. Issue 100 (September 2017) - Bayat, M.; Andersen, L.V.; Ibsen, L.B.; Clausen, J.
Abstract: The well-known p - y curve method provides soil-structure interaction that does not account for the pore pressure effect for dynamic analysis of offshore wind turbines (OWTs). In order to avoid overly conservative designs, reliable estimates of the dynamic response should be taken into account. The turbine is introduced using a simplified model to assess the eigenfrequencies and modal damping, accounting for pore water flow and excess pore pressure around the monopile. Thus the effect of pore pressure and load frequency are illustrated by implementing a poroelastic model to present more realistic dynamic properties and compare them with results obtained by the p - y curve method. A cyclic loading is considered and the soil stiffness based on the Winkler and Kelvin models is calculated and compared while the soil damping for the Kelvin model is computed. Developed finite element programs are employed to present the results for a two-phase system consisting of a solid skeleton and pore fluid, based on the u - P formulation. Here, u is grain displacement and P is pore water pressure. The developed codes have been validated with commercial software and are implemented to perform free vibration tests to evaluate the eigenfrequencies. A linear poroelastic material model is utilized. An equivalent masses-dashpots-springs system at the pile-cap level is calculated and compared by using Winkler and Kelvin models to highlight the effect of pore pressure and load seepage damping. Highlights: Sandy soil can present reduction of soil stiffness and maximum value of damping. Equival ent dashpot and mass at the pile cap are highly dependent on the soil type. Dynamic soil stiffness for offshore monopile foundation is calculated. Soil damping around offshore monopile wind turbine foundation is calculated. The effect of pore pressure and load frequency is illustrated.